2020
DOI: 10.1158/1535-7163.mct-19-0947
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Syk–PI3Kγ Inhibits Antitumor Immunity: SRX3207, a Novel Dual Syk–PI3K Inhibitory Chemotype Relieves Tumor Immunosuppression

Abstract: ◥ Macrophages (MÈ) play a critical role in tumor growth, immunosuppression, and inhibition of adaptive immune responses in cancer. Hence, targeting signaling pathways in MÈs that promote tumor immunosuppression will provide therapeutic benefit. PI3Kg has been recently established by our group and others as a novel immuno-oncology target. Herein, we report that an MÈ Syk-PI3K axis drives polarization of immunosuppressive MÈs that establish an immunosuppressive tumor microenvironment in in vivo syngeneic tumor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 42 publications
0
45
0
Order By: Relevance
“…While iNOS is typically induced by M1 macrophages, studies have found that M2-like TAMs express iNOS at lower levels than M1 macrophages and these low levels of NO produced by TAMs inhibits tumor cell apoptosis and serves a cytoprotective function ( 126 128 ). Recent studies have shown that PTEN/PI3K/AKT signaling axis and Syk-Rac2 signaling axis promotes the stabilization of HIF1/2α in TAMs and polarization of macrophages into immunosuppressive phenotype in solid tumors ( 129 132 ). The inhibition of these signaling axes induces degradation of HIF1/2α in a proteasome-dependent manner and suppresses tumor growth and metastasis in solid tumors.…”
Section: Tams In Neuroblastomamentioning
confidence: 99%
See 3 more Smart Citations
“…While iNOS is typically induced by M1 macrophages, studies have found that M2-like TAMs express iNOS at lower levels than M1 macrophages and these low levels of NO produced by TAMs inhibits tumor cell apoptosis and serves a cytoprotective function ( 126 128 ). Recent studies have shown that PTEN/PI3K/AKT signaling axis and Syk-Rac2 signaling axis promotes the stabilization of HIF1/2α in TAMs and polarization of macrophages into immunosuppressive phenotype in solid tumors ( 129 132 ). The inhibition of these signaling axes induces degradation of HIF1/2α in a proteasome-dependent manner and suppresses tumor growth and metastasis in solid tumors.…”
Section: Tams In Neuroblastomamentioning
confidence: 99%
“…One strategy to repolarize macrophages in vivo is the inhibition of Syk-Rac2 signaling axis. Our group has identified a novel signaling pathway by which α 4 β 1 integrin and CSF receptor activates Syk-PI3Kγ-Rac2 axes to polarize macrophages into immunosuppressive phenotype ( 130 132 ). Rac2 is a hematopoietic GTPase and our studies have shown that macrophage deletion of Rac2 blocks tumor growth in syngeneic NB9464 model of neuroblastoma ( 130 ).…”
Section: Tam Targeted Immunotherapy In Neuroblastomamentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that down-regulation of LYN inhibited the proliferation, migration and invasion of melanoma cell lines via suppressing PI3K/AKT signaling pathway [43]. Combined treatment of SYK inhibitor and PI3K inhibitor induced anti-tumor immune responses via promoting pro-inflammatory macrophage phenotype and activating CD8 + T cells [44]. LCK was also reported to activate T cell via facilitating costimulatory molecule CD28-mediated signal transduction and LAT phosphorylation [45].…”
Section: Kinase Targets Of Hub Genesmentioning
confidence: 99%